History Page: Leaders in MSK Radiology Karl Dussik, 1908–1968: Pioneer of MSK Ultrasonography - Sudoł-Szopińska, Iwona; Martinoli, Carlo; Panas-Goworska, Marta (Seminars in Musculoskeletal Radiology, 2021)
This history page in the series “Leaders in MSK Radiology” is dedicated to the memory and achievements of Karl Theodore Dussik, the Austrian neurologist and psychiatrist from the University of Vienna who is recognized as the pioneer of ultrasonography.
Keywords: Karl Dussik; ultrasonography; history